Protection of a Human, Human Rights and International practices in Counterfeiting Medicines: Management and Administration Issues in the Globalized Environment - Ilkov, V. V.; Lysenko, T. V.; Myrnyi, S. P.; Tuchkov, S. S.; Shekhovtsova, I. O.; Ілков, В. В.; Лисенко, Т. В.; Мирний, Сергій Петрович; Тучков, С. С.; Шеховцова, І. О. (My University, 2020)
The article highlights the problematic issues of implementing of the best international practices in protection of a human and human rights, and counterfeiting medicines in the context of globalization. Every state exists for man, for the protection of universally recognized rights and freedoms. counterfeiting of medical products and other similar crimes require attention in any country in the world. Counterfeiting is not an exception in developed countries in Europe, such as the Netherlands, Belgium, Sweden, Switzerland, Finland, Norway, Denmark, and Austria. This problem is global for, both, legal and public administration science. It is widespread throughout the world, and the negative effects of this crime have severe consequences that affect people's lives and health. The purpose of the article is to study and summarize the best international experience in protection of a human, his rights and in the fight against counterfeiting of medicines, as well as to explore the problems of its implementation in the context of globalization. The research material is a modern international regulatory framework, which governs the struggle against counterfeiting of medicinal products, foreign and domestic scientific works of specialists. The system method, structural and functional method, techniques of logical method, method of legal statistics, legal modeling were used in writing the article. Techniques of logical method such as analysis, synthesis, deduction, and induction were also reviewed. The general theoretical characteristics of the best international experience in combating counterfeiting of medicinal products has been studied and represented. In addition, the generalization and systematization of studies of its implementation in the context of globalization have been made. Theoretical generalization and new ways of the scientific problem solving, which are manifested in the definition of the theoretical and legal foundations of the fight against counterfeiting in medicines under the conditions of globalization, are made. It is possible to do this by adopting programs for the development and support of scientific and practical work in the creation of new international normative legal acts, amendments to legislation. Because of the research, a number of theoretical generalizations, suggestions, and practical recommendations are represented.
Keywords: counteraction management; counterfeiting of medicines; globalization; digitization; protection of a human and human rights